Fracture of european cultural consciousness of the XIX-XX centuries: change of paradigm - O. A. Pushonkova, (Ukrainian Cultural Studies, 2018)
The article analyzes the phenomenon of cultural fracture (shift, breakdown), which reflects the nature of transformational processes in the culture of the end of the XIX — early XX century and focuses on the mechanisms of transmission of the cultural and historical experience of mankind. The dynamic character of changes in the European cultural consciousness on the verge of the XIX and XX centuries, the transition from the classical model of cultural interpretation to the non-classical and post-classical, the role of everyday life in the "inalienable" states of culture has been researched. The connection between criticism of culture and correlation between scientific and art world views of the end of the XIX and the beginning of the XX century has been revealed. The consequences of a total cultural fracture in the human consciousness of European culture in the projections of cultural-traumatic discourse are revealed through the conceptual topography of the XX century culture. The culture of everyday life, which arises in the XIX century as a culture of comfort, has become the cause of a collision between alternative spiritual states of culture, which also caused a situation of fracture. The fracture of culture reveal the inner essence of culture and in the conditions of the anthropological crisis form a new dynamic model of the worldview that includes the past and the future at the same time. If in the classical version of the philosophy of culture the crisis is perceived as a source of eschatological sentiment, then in the non-classical one it acquires signs of an existential crisis, which outlines a new type of "split" cultural consciousness. The sharp change in ideological orientations concentrates the attention of researchers on transitional states of culture, which has a huge evaluetive potential, as the need for their inclusion in the dynamism and the logic of cultural development (O. Losev, N. Mankovskaya, G. Knabe, and others). Actualization in the mental field of modern culture of new meanings and metaphorical concepts - "labyrinth", "rhizome", "fold", "crossroads" is the consequence of the continuation of permanent transition, the state of search in situation of uncertainty. The situation of the XX — beginning of the XXI century is not a fracture, because it is rather a deepening of the tendencies that were laid in the late XIX - XX centuries. Of course, fundamentally new phenomena arise, a new topography of culture is formed, in connection with the advent of information technologies appear new types of identity, which acquires signs of "drifting", cultural-traumatic discourse is formed. However, these processes can rather be defined not as a radical "revaluation of values", but as a "dispersal" of new values acquired during the XX century, "improvement" of new formats of the culture of everyday life, the problems of which arise in the XIX century.
Keywords: cultural consciousness, value, culture of everyday life, cultural tradition, cultural fracture, transitional states of culture, cultural trauma, cultural traumatic discourse